Terahertz radiation in ophthalmology (review) - A. G. Zabolotniy; I. A. Geiko; L. M. Balagov (Acta Biomedica Scientifica, 2021)
Terahertz (THz) radiation is one of the new, intensively studied interdisciplinary fi elds of scientifi c knowledge, including medicine, in the fi rst decades of the 21st century. At the beginning of this article (review), in a brief form, the basic statements on THz radiation, the main parameters and properties are presented; the modern THz biophtonics technologies used in biology and medicine are considered – THz refl ectometry, THz spectroscopy methods. Then a number of directions and examples of possible use of THz technologies in biology and medicine, including pharmaceuticals, are given. The main part of the review presents the progress of experimental research and the prospects for the clinical application of medical technologies of THz spectroscopy, THz imaging, in ophthalmology in the study of the morphological and functional state of the ocular surface structures, diagnosis, medical testing, and treatment of ophthalmopathology of the ocular surface. The article concludes with a review of experimental studies on the safety of using THz waves for medical diagnostics and treatment of ophthalmopathology. In the fi nal part, the main problems and prospects of introducing medical THz technologies into the clinical practice of an ophthalmologist are considered.